What Is the Role of Mental Health in Primary Total Knee Arthroplasty? - Lavernia, Carlos J. (Clin Orthop Relat Res, 2014)
BACKGROUND: Psychological distress has been associated with inferior scores for pain after total knee arthroplasty (TKA). However, its relationships with scores and arthrofibrosis after TKA remain unclear. QUESTION/PURPOSES: The objectives of this study were (1) to assess patient-reported outcomes (PROs), including Knee Society (KS) scores, of those patients who developed arthrofibrosis and underwent manipulation and compare them with a control group; and (2) in patients with arthrofibrosis who underwent manipulation, to determine PROs and KS scores of those with psychological distress and those without it. METHODS: During a 17-year period (August 1992 to October 2009), a total of 1952 TKAs were performed and included in our prospectively collected joint registry database; 1248 procedures had a postoperative followup of at least 2 years (mean, 5 years; range, 2–16 years). Among them, 57 knees (53 patients) developed arthrofibrosis and underwent manipulation under anesthesia after the index procedure. This group was compared with a matched group (by age, sex, race, and ethnicity) of 63 knees (58 patients) without arthrofibrosis. Demographics, preoperative and postoperative Quality of Well-Being scale (QWB-7), SF-36, WOMAC, and The KS knee and function scores were prospectively collected and retrospectively analyzed. Patients with < 52 points on the SF-36 Mental Component Summary subscale were considered in psychological distress for all comparisons. Active knee flexion and KS range of motion (ROM) were used as objective motion measures. Minimum followup was 2 years (mean, 5 years; range, 2–16 years). RESULTS: Patients who developed arthrofibrosis had worse KS function scores before TKA than did patients in the nonarthrofibrosis control group (mean 27, SD 20.5 versus 37, SD 19.3; p = 0.006). Patients with arthrofibrosis and psychological distress, before TKA and when compared with patients with arthrofibrosis but without distress, had worse QWB-7 (0.490 versus 0.547; p < 0.001) and worse WOMAC stiffness (4.92, versus 3.22; p = 0.005), respectively. Postoperatively, patients with arthrofibrosis and distress also had worse QWB-7 (0.537 versus 0.627; p = 0.002). CONCLUSIONS: Patients with arthrofibrosis and psychological distress perceived themselves preoperatively as having worse knee and overall health status than those with arthrofibrosis but without distress. In view of this, expectations after TKA should be particularly addressed in those patients with poor function and psychological distress. Further investigations, making use of tools specifically designed to ascertain depression, are warranted. LEVEL OF EVIDENCE: Level III, prognostic study. See the Instructions for Authors for a complete description of levels of evidence.